Efektivitas Indikator MACD Dan RSI Dalam Menentukan Sinyal Jual Beli Saham Top 4 Big Banks Di Indonesia - Anggraini, Sisilia; Imron, Habibulloh (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2025)
This study aims to examine the effectiveness of the technical indicators Moving Average Convergence Divergence (MACD) and Relative Strength Index (RSI) in generating buy and sell signals for the four largest banks in Indonesia—BBCA, BBRI, BMRI, and BBNI—during the period from May 23, 2023, to May 23, 2024. A quantitative approach with a descriptive analytical method was applied to secondary data in the form of daily stock closing prices obtained from the Indonesia Stock Exchange. The results show that the MACD indicator provides more accurate and consistent signals compared to the RSI, with buy signal accuracy reaching 87.5% and sell signals at 85.2%. Conversely, RSI showed buy signal accuracy at 83.3% and sell signal accuracy at 72.7%. The chi-square test also indicates a statistically significant relationship between both indicators and actual stock price movements. While RSI is better suited for sideways markets, MACD proves to be more effective in trending conditions, which are typical in the banking sector. These findings offer practical implications for investors in making technical analysis-based investment decisions in the Indonesian stock market.